Acute effects of cluster and rest redistribution set structures on mechanical, metabolic, and perceptual fatigue during and after resistance training: A systematic review and meta-analysis - Jukic, I.; Garcia Ramos, A.; Helms, E. R.; McGuigan, M. R.; Tufano, J. J. (Sports Medicine, 2020)
Background: The alteration of individual sets during resistance training (RT) is often used to allow for greater velocity and power outputs, reduce metabolite accumulation such as lactate and also reduce perceived exertion which can ultimately affect the resultant training adaptations. However, there are inconsistencies in the current body of evidence regarding the magnitude of the effects of alternative set structures (i.e., cluster sets and rest redistribution) on these acute mechanical, metabolic, and perceptual responses during and after RT.